Analisis Penilaian Tingkat Kesehatan Bank Menggunakan Metode Camels Pada PT Bank Syariah Mandiri, Tbk - Yekti Rahajeng (Fakultas Ekonomi Universitas Panca Marga, 2016)
The purpose of this research is analyze the bank soundness of PT Bank Syariah Mandiri period 2009-2011 when assessed using the CAMELS. The factors examined in this research include the ratio of CAR (Capital Adequacy) for capital, KAP (Earning Assets) for asset quality, GCG implementation of self assessment for management factor, NOM (Net Operating Margin) for profitability, STM (Short Term Mismatch) for liquidity, and MR (Market Risk) for sensitivity to market risk. The result of this research indicate that PT Bank Syariah Mandiri, Tbk period 2009-2011 has composite ranking scores 2, which reflects that the bank’s relatively good health and able to overcome the negative influence of economic conditions and the financial industry, but the bank still has minor flaws that can be readily handled by routine measures. Keywords : bank soundness, CAMELS, composite rating